Pengaruh Jumlah Anggota, Jumlah Simpanan, Jumlah Pinjaman dan Jumlah Modal Kerja Terhadap Sisa hasil Usaha (SHU) Koperasi Simpan Pinjam (KSP) di Kabupaten Badung Provinsi Bali - ayuk, made taman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; Volume.02.No.09.Tahun 2013, 2013)
Koperasi is one of the economic force that drive the growth of the national economy SHU or Koperasi’s profit is also one important element in improving the welfare of its members, including the savings and credit of Koperasi (KSP). The objectives of this research are as follows : 1) to determine the effect of the number of members, number of members’ savings, the loan amount and the number of members working capital simultaneously on Koperasi’s profit (SHU) at the savings and credit of Koperasi (KSP) of Badung Regency; 2) to determine the effect of the number of members, number of members’ savings, the loan amount and the number of members working capital partial on Koperasi’s profit (SHU) at the savings and credit of Koperasi (KSP) of Badung Regency; 3) to determine the most dominant variable influence Koperasi’s profit (SHU) at the savings and credit of Koperasi (KSP) of Badung Regency. This research, which is located at Badung regency. The analysis 34 from 46 of KSP with timeseries with 2007-2011. Data were collected analysis regression by random sampling technique. According to the analysis of the data, can be known that the amount of the savings and credit of Koperasi (KSP) members, and the amount of working capital of the savings and credit of Koperasi (KSP) simultaneously significant effect of Koperasi’s profit (SHU), and also partially positive and significant of net income cooperatives in Badung. Usually variable the amount of members’s savings, the amount of members’s loan simultaneously isn’t significant effect of Koperasi’s profit (SHU) .Variable the amount of working capital is the dominant factor that influence Koperasi’s profit (SHU). Based on these results to suggest the need for efforts to reduce lending rates and administrative costs, as it will influence the behavior of members of the cooperative in making loans at savings and loans co-operative unit. If the interest on the loan and reduced administrative costs, members will be more interested in making the loan, so the savings and loan business unit revenue increased and ultimately the level of member participation is greater. Keywords :  Koperasi’s profit (SHU), the amount of the savings and credit of Koperasi (KSP) members, the amount of members’s savings, the amount of members’s loan, and the amount of working capital.
Keywords: Koperasi’s profit (SHU), the amount of the savings and credit of Koperasi (KSP) members, the amount of members’s savings, the amount of members’s loan, and the amount of working capital.